Evaluation of a gel diffusion precipitin test for porcine parvovirus - Too, H. L.; Seaman, J. T.; Littlejohns, R.; Love, R. J. (Wiley, 1983)
The use of a gel diffusion precipitin (GDP) test for the detection of porcine parvovirus (PPV) infection in pigs is described. The close correlation between gel diffusion precipitin and haemagglutination inhibiting (HI) antibody titres indicates that, with careful standardisation, a high level of sensitivity can be achieved with the GDP test and that it is a simple and relatively inexpensive alternative to the more commonly used HI test. Experimental infection of 2 groups of pigs showed that GDP and HI antibody responses were closely correlated and that GDP antibodies to PPV persisted for at least 41 weeks after infection. In a commercial herd study, serological evidence of declining passive immunity and subsequent acquisition of active immunity was demonstrated by measuring the GDP and HI antibody titres in sequential serum samples of pigs from a known PPV endemic farm. The GDP test described was shown to be less sensitive than haemagglutination (HA) in the detection of viral antigen but was, nevertheless, considered useful as a simple screening test for the amounts of antigen usually present in PPV infected mummified foetuses